Taking a long-term approach to the development of weightlifting ability in young athletes - Morris, S. J.; Oliver, J. L.; Pedley, J. S.; Haff, G. G.; Lloyd, R. S. (Strength and Conditioning Journal, 2020)
Despite previous misconceptions, youth participation in weightlifting is now recognized as safe and beneficial when delivered, programed, and monitored by a qualified professional. This article explores teaching progressions to help coaches periodize weightlifting training for young or novice athletes, with consideration to the theoretical concepts underpinning long-term athletic development. It is hoped that the structured and progressive guidelines presented in the current article will help coaches develop the weightlifting performance of their young athletes in a safe and effective manner.